Experiential Learning of Using Digital Tools in Construction Management Education - Sh Said, Sheikh Ali Azzran; Mohd Yussof, Farrah Norizzah (Online Journal for TVET Practitioners, 2023)
The Fourth Industrial Revolution (IR4.0) is gradually reshaping the entire construction industry. It is not an option that skills and abilities in a wide range of digital technologies should be part of the construction management curriculum. The sheer lack of skills and expertise in the shift to digital construction is related to the insufficiency of hands-on activities using various digital tools. This study outlines the experience learning of utilising digital tools in construction management education. The purpose of this article is to investigate the extent to which Experiential Learning Theory (ELT) influences students’ perceptions of digital tools. The student association in the construction management programme offered at Universiti Teknologi MARA (UiTM) designed and organised a hands-on workshop activity approach to address the issue of lack of proficiency in using digital tools such as Autodesk Revit (BIM system), Microsoft Excel (Quantity Take-Off). The method begins with a basic grasp of digital tools for construction-related applications. Then, step by step, explores the computer interface ribbons, shortcuts, and associated tabs. The proposed method is examined in faculty computer laboratories by employing practical learning for both digital tools (i.e. Revit and Excel) in either creating a three-dimensional (3D) BIM Model or the capacity to calculate material amounts. Based on the assessment results, the strategy helps students master the digital tools and implement such activities in their official course module.